2020
DOI: 10.1136/bmjopen-2019-035957
|View full text |Cite
|
Sign up to set email alerts
|

How do aggression source, employee characteristics and organisational response impact the relationship between workplace aggression and work and health outcomes in healthcare employees? A cross-sectional analysis of the National Health Service staff survey in England

Abstract: ObjectivesTo examine the prevalence of aggression in healthcare and its association with employees’ turnover intentions, health and engagement, as well as how these effects differ based on aggression source (patients vs colleagues), employee characteristics (race, gender and occupation) and organisational response to the aggression.DesignMultilevel moderated regression analysis of 2010 National Health Service (NHS) survey.Setting147 acute NHS trusts in England.Participants36 850 participants across three occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…These findings suggest that in UK, aggression episodes might occur (or are reported) more frequently than in other European countries [22]. In general, however, in European hospital psychiatric settings, preoccupying rates of both verbal and physical violence are enacted by patients, and this condition has remained unvaried over the last two decades, according to recent studies based on specifically developed questionnaires and interviews carried out in Norway [23], England [24], and Italy [25].…”
Section: Aggression In Psychiatric Settingsmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings suggest that in UK, aggression episodes might occur (or are reported) more frequently than in other European countries [22]. In general, however, in European hospital psychiatric settings, preoccupying rates of both verbal and physical violence are enacted by patients, and this condition has remained unvaried over the last two decades, according to recent studies based on specifically developed questionnaires and interviews carried out in Norway [23], England [24], and Italy [25].…”
Section: Aggression In Psychiatric Settingsmentioning
confidence: 93%
“…A UK-based investigation among 194 subjects with a first episode psychosis using the Psychiatric and Personal History Schedule (PPHS) [26] showed that almost 40% of cases enacted an aggressive behavior and that approximately half of these were physically violent [27]. A very recent survey promoted by the UK National Health System [24] using ad hoc developed measures and existing instruments altered to fit the research intents found that the average number of aggressive incidents in mental health/learning disability trusts was over three times the average for all trusts.…”
Section: Aggression In Psychiatric Settingsmentioning
confidence: 99%
“…Reported that workplace aggression among workers was low because organization designed intervention to prevent workplace aggression and reduce burnout, supervisor have good communication with staff and the organization takes into account the workers' complaints. Furthermore, result Cheng, Dawson, Thamby, Liaw & King, (2020) (32) . Revealed that aggression related workplace was the phenomenon is difficult to occur among nursing staff because have the responsibility to provide safe and healthy working environment and to protect other people in the workplace from conflicts or situations that may cause physical and psychological injury or harm.…”
Section: Resultsmentioning
confidence: 98%
“…High quality quantitative studies on NHS job attrition are less common. Many of them suffer from small samples or lack adequate regression modelling to robustly estimate relationships [14,[27][28][29][30][31], though some larger sample regression-based studies do exist [32][33][34][35][36]. For registered nurses, work pressure and work-related stress emerged from structural equation modelling (n = 16,707) as the strongest positive correlates with intent to leave the NHS (other than organisation type) [32].…”
Section: Background Literaturementioning
confidence: 99%
“…For registered nurses, work pressure and work-related stress emerged from structural equation modelling (n = 16,707) as the strongest positive correlates with intent to leave the NHS (other than organisation type) [ 32 ]. Aggression from both colleagues and patients is significantly related to the intent to leave [ 33 ], though it is not clear from the study how important this reason is relative to others. Hann et al [ 36 ] and Fletcher et al [ 34 ] both study GP survey data in samples >1000.…”
Section: Introductionmentioning
confidence: 99%